2022
DOI: 10.1093/noajnl/vdac059
|View full text |Cite
|
Sign up to set email alerts
|

Leptomeningeal disease and tumor dissemination in a murine diffuse intrinsic pontine glioma model: implications for the study of the tumor-cerebrospinal fluid-ependymal microenvironment

Abstract: Background Leptomeningeal disease and hydrocephalus are present in up to 30% of patients with diffuse intrinsic pontine glioma (DIPG), however there are no animal models of cerebrospinal fluid (CSF) dissemination. As the tumor-CSF-ependymal microenvironment may play an important role in tumor pathogenesis, we identified characteristics of the Nestin-tumor virus A (Nestin-Tva) genetically engineered mouse model (GEMM) that make it ideal to study the interaction of tumor cells with the CSF and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…11 ). These differences may be due to increased transependymal CSF flow across the lateral ventricle walls 52 , 53 .…”
Section: Resultsmentioning
confidence: 99%
“…11 ). These differences may be due to increased transependymal CSF flow across the lateral ventricle walls 52 , 53 .…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study provided compelling preclinical evidence that sonobiopsy enriched circulating RNA, DNA, and proteins in small and large animal models [24][25][26][27][28] . Recently, we found that sonobiopsy improved the detection sensitivity of GBM-specific EGFRvIII mutation from 7.14% to 64.71% and TERT C228T from 14.29% to 45.83% in a mouse GBM model.…”
Section: Introductionmentioning
confidence: 93%